On the Predicament and Future Reform Path of the Dispute Settlement System of the WTO (Asian Journal of Social Science Studies, 2022)
The dispute settlement system of the WTO has made great contributions to international trade, but its defects are becoming more and more obvious after practical development. Coupled with the obstruction of some members to the normal operation of the dispute settlement system of the WTO, the Appellate Body is now lockout, and the WTO is in a deep crisis. The emergence of MPIA alleviates this crisis to a certain extent and has certain feasibility at the same time. However, MPIA cannot be used as a long-term solution to the dilemma of the WTO. Therefore, it is still necessary to explore the future reform of the dispute settlement system of the WTO.